Compilers : Principles, techniques and tools - Aho, Alfred V. (Noida: Pearson, 2007)
Compilers: Principles, Techniques and Tools, known to professors, students, and developers worldwide as the "Dragon Book," is available in a new edition. Every chapter has been completely revised to reflect developments in software engineering, programming languages, and computer architecture that have occurred since 1986, when the last edition published. The authors, recognizing that few readers will ever go on to construct a compiler, retain their focus on the broader set of problems faced in software design and software development.
Include bibliographical references; Appendix A-965, B-992p; Index 993-1009p
Keywords: Code generation; Computer language processor; Computer-syntax directed translator; Syntax directed translator; Computer Science